Development economics - Cluines-Ross, Anthony; Forsyth, David; Huq, Mozammel (London : McGraw-Hill, 2009)
This textbook presents a concise and up-to-date examination of the field of development economics, bringing together historical perspectives, current issues and policy implications.
Includes bibliographical references and index.
rua 03/01/14
Loans
Keywords: Economic development .